Changes in the consumption of isoflavones, omega-6, and omega-3 fatty acids in women with metastatic breast cancer adopting a whole-food, plant-based diet: post-hoc analysis of nutrient intake data from an 8-week randomized controlled trial - Lee, Jean; Campbell, Erin K.; Culakova, Eva; Blanchard, Lisa M.; Wixom, Nellie; Peppone, Luke J.; Campbell, Thomas M. (Frontiers in Nutrition, 2024)
Background: Diets rich in minimally processed plant-based foods are recommended to breast cancer patients, and some may have an interest in whole-food, plant-based (WFPB) diets that avoid animal-based foods, added fats, and refined sugars. Within WFPB diets, the intakes of isoflavones, omega-6 polyunsaturated fatty acids (n-6 PUFAs), and omega-3 polyunsaturated FAs (n-3 PUFAs), which have been discussed in reference to breast cancer outcomes, have not been well characterized.Methods: Women with stage IV breast cancer on stable therapy were randomized 2:1 into 1) a WFPB intervention (N=21) or 2) usual care (N=11) for 8 weeks. Three meals per day were provided. Outcomes presented here include dietary intake of isoflavones, n-3 and n-6-PUFAs, which were assessed using three-day food records at baseline and 8 weeks. Baseline and 8-week mean intake within groups were compared using the Wilcoxon signed-rank test and between control and intervention groups by a two-sample t-test.Results: The WFPB intervention participants increased their daily consumption of total isoflavones from a mean of 0.8 mg/day to 14.5 mg/day (p <0.0001) and decreased the n-6:n-3 ratio of their diet from a mean of 9.3 to 3.7 (p<0.0001). Within the WFPB group, linoleic acid (n-6 PUFA) consumption decreased by a mean of 3.8 g (p=0.0095), from 12.8 g/day to 9.0 g/day; total n-3 PUFA consumption increased by a mean of 1.1 g (p=0.0005), from 1.6 g/day to 2.7 g/day.Conclusion: Transitioning to a WFPB diet resulted in significantly increased isoflavone intake and decreased n-6:n-3 ratio in women with breast cancer.